Prediction in logistics using functions with flexible structure - Fadina, Olga; Mazūra, Mindaugas (Transport, 2003)
The economic forecasts are aimed at determining major trends of logistics development as well as defining the particular aims and objectives oftheir functioning. Therefore, the prediction in logistics should reveal major changes in micro and macro factors to obtain the probability criteria of quantitative and qualitative evaluation of the dynamics of logistics activities required by the firm manager. Some methods of predicting the development of the logistics system based on the application of functions with flexible structure and of evaluating the accuracy and truth (reliability) of forecasts are offered. First Published Online: 19 Dec 2011